Developing students' communicative writing skills through blogging / Nurul Fadilah, Akmal Akmal and Kamisah Ariffin - Abdullah, Nurul Fadilah; Abdullah, Akmal Akmal; Ariffin, Kamisah (Universiti Teknologi MARA, 2020)
Blogs have gained o ularity among language teachers as a tool to develo students' writing skills. However, using blogs in teaching writing has not been widely ractised in Indonesia de ite the ositive effects on students' learning as re orted in the literature. This a er examines the develo ment of students' communicative writing skills through blogging. The data were collected from students' writing based on different themes osted in a class blog over a five-week eriod. Using Franker's ELT blog rubric as a framework for analysis, the findings were classified into four codes of communicative skills in writing: creativity, critical thinking, voice and comment. The findings indicate a general im rovement on the students' communicative skills in writing based on these codes. Students also res onded ositively towards the use of blogging in develo ing their communicative skills in writing. Not only blogging hel ed to develo their minds critically and evaluatively, they were able to write their thoughts and res ond to others' oint of view freely without the resence of the instructor and fellow friends. Such findings indicate that with advance of technology in education, blogs can be an alternative medium for teaching writing in class, es ecially in this IR4.0 era.